(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2015)
HRM i.e Human Resource Management is a strategic and comprehensive approach to manage Manpower at workplace & working environment. Earlier HRM was considered as a job responsible for the attracting, re cruiting, selecting, training, assessment and compensation of employees while ensuring compliance with employment and labor laws. Now a days this profession is considered as a passion by youngsters as it involves many innovations like succession planning, business continuity planning, workforce diversity, labor relations and some aspects of merg ers and acquisitions. HRM also has impact of Global, Political, Social, Economic & techno logical trends of the society & work culture. The paper focuses on how upcoming techniques can be taken up and its impact on different management decisions and challenges arising for the organization etc.The paper discusses the various issues related to HRM. The paper closes with recommendations and strategies which can be adopted by the orga nization for solving the issues.